PENGARUH EKSTRAK DAUN KELOR (Moringa oleifera L) TERHADAP PERTUMBUHAN, KELULUSHIDUPAN, KELIMPAHAN BAKTERI, DAN GAMBARAN HISTOLOGI USUS UDANG VANAME (Litopenaeus vannamei) - Maskinasih, Roro; Ayu Angga Pebriani, Dewa; Gde Sasmita Julyantoro, Pande (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
The purpose of this study was to determine the effect of moringa leaf extract (Moringa oleifera) on growth, immunity, digestive health and water quality of vannamei shrimp cultivation media (Litopenaeus vannamei). This study used the Complete Random Design method which consisted of 2 treatments with 6 replicates each. The treatment consisted of A (negative control without the addition of moringa leaf extract) and B (feeding with moringa leaf extract enhancer 1:1). Data analysis used a statistical paired samples T-test. The results of the study showed that moringa leaf extract did not have a significant effect on the growth of vannamei shrimp but had a significant effect on the survival of vannamei shrimp. The average bacterial abundance in treatment A was 7.58 (3.8×107 CFU/mL) and treatment B was 7.64 (4.4×107 CFU/mL). Meanwhile, histological results in treatment A found tissue structure damage (necrosis) and in treatment B there was no tissue structure damage. The water quality parameters measured during the maintenance period, both temperature, pH, dissolved oxygen and salinity are still at the optimal value. Based on these results, moringa leaf extract can be used as a phytoimmunostimulant in vannamei shrimp cultivation activities.